2018 International Conference on 3D Vision (3DV) 2018
DOI: 10.1109/3dv.2018.00032
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Estimate Indoor Lighting from 3D Objects

Abstract: In this work, we propose a step towards a more accurate prediction of the environment light given a single picture of a known object. To achieve this, we developed a deep learning method that is able to encode the latent space of indoor lighting using few parameters and that is trained on a database of environment maps. This latent space is then used to generate predictions of the light that are both more realistic and accurate than previous methods. To achieve this, our first contribution is a deep autoencode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…Hold-Goeffroy et al [14] learned outdoor lighting using a physically-based sky model. Weber et al [32] estimated indoor environment lighting from an image of an object with known shape. Zhou et al [37] estimated lighting, in the form of Spherical Harmonics, from a human face image by assuming a Lambertian reflectance model.…”
Section: Related Workmentioning
confidence: 99%
“…Hold-Goeffroy et al [14] learned outdoor lighting using a physically-based sky model. Weber et al [32] estimated indoor environment lighting from an image of an object with known shape. Zhou et al [37] estimated lighting, in the form of Spherical Harmonics, from a human face image by assuming a Lambertian reflectance model.…”
Section: Related Workmentioning
confidence: 99%
“…Inverting this image formation process to recover lighting (or any of these other intrinsic properties) is severely underconstrained. Typical solutions to this problem rely on inserting an object (a light probe) with known geometry and/or reflectance properties in the scene (a shiny sphere [5], or 3D objects of known geometry [9,34]). Unfortunately, having to insert a known object in the scene is limiting and thus not easily amenable to practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Debevec et al [3] first showed that photographs of a mirrored sphere with different exposures can be used to compute the illumination at the sphere's location. Subsequent works show that beyond mirrored spheres, it is also possible to capture illumination using hybrid spheres [4], known 3D objects [24], object's with know surface material [8], or even human faces [1] as proxies for light probes.…”
Section: Related Workmentioning
confidence: 99%